2022
DOI: 10.5812/jhealthscope.120968
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Manganese Among Welders: Association Between Airborne Manganese Concentration and Blood Manganese Levels

Abstract: Background: Manganese (Mn) is an essential element for the human body, but it can cause adverse effects on the Central Nervous System at high doses. Exposure to manganese fumes during welding can harm welders' health. Objectives: The current study aimed to measure manganese produced by shielded metal arc welding (SMAW) in the breathing zone air and blood of welders and investigate the relationship between manganese concentrations in air and blood. Methods: In this descriptive-analytical cross-sectional study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Several studies have shown that people poisoned with organophosphate compounds show cardiovascular symptoms such as hypotension and arrhythmia (5,6). Also, other studies have shown environmental and occupational exposure can harm health (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that people poisoned with organophosphate compounds show cardiovascular symptoms such as hypotension and arrhythmia (5,6). Also, other studies have shown environmental and occupational exposure can harm health (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…The separation of anthracene from coal tar is the most economical way of production. Anthracene is used as a paint precursor (15,16). Benzofluoranthenes, such as benzo(y)fluoranthene and benzo(k)fluoranthene, are among the most commonly detected environmental polynuclear aromatic hydrocarbons, occurring in gasoline engine exhaust, urban air, cigarette smoke, soil, water, and broiled and smoked foods (17).…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%